Cell-Based Therapies Used to Treat Lumbar Degenerative Disc Disease: A Systematic Review of Animal Studies and Human Clinical Trials. (14th May 2015) - Oehme, David; Goldschlager, Tony; Ghosh, Peter; Rosenfeld, Jeffrey V.; Jenkin, Graham
Abstract : Low back pain and degenerative disc disease are a significant cause of pain and disability worldwide. Advances in regenerative medicine and cell-based therapies, particularly the transplantation of mesenchymal stem cells and intervertebral disc chondrocytes, have led to the publication of numerous studies and clinical trials utilising these biological therapies to treat degenerative spinal conditions, often reporting favourable outcomes. Stem cell mediated disc regeneration may bridge the gap between the two current alternatives for patients with low back pain, often inadequate pain management at one end and invasive surgery at the other. Through cartilage formation and disc regeneration or via modification of pain pathways stem cells are well suited to enhance spinal surgery practice. This paper will systematically review the current status of basic science studies, preclinical and clinical trials utilising cell-based therapies to repair the degenerate intervertebral disc. The mechanism of action of transplanted cells, as well as the limitations of published studies, will be discussed.